Compact 1- and 2-bit coding metamaterial for RCS reduction application in terahertz frequency - Tayaallen Ramachandran; Mohammad Rashed Iqbal Faruque; K.S. Al-mugren (Ain Shams Engineering Journal, 2024)
This work focuses on 1- and 2-bit coding metamaterials by designing unit cell structures, also known as binary elements, that possess 0-, 90-, 180-, and 270-degree phase responses. Several parametric studies are mainly investigated, for instance, various coding sequence patterns and a few numbers of lattices likely 4, 8, and 12 in each bit. The RCS reduction analysis revealed a promising outcome where the distinct coding sequences exhibited way better reduction behaviour than others. For instance, coding sequences likely CS3, CS4, and CS5 exhibit excellent reduction behaviour when the lattices increase from 4 to 12. However, the 2-bit coding metamaterial exhibits superior reduction behaviours in RCS values, where the maximum points reached when adopting the CS5 design ranged from −75.2 to −55.6 dBm2.Concisely, the proposed coding metamaterial satisfied the target of this investigation to gain optimal RCS reduction by adopting both 1- and 2-bit design structures for terahertz frequency.